The Teatro Sant'Angelo : cradle of fledgling opera troupes - Eleanor Selfridge-Field (Musicologica Brunensia, 2018)
Many smaller theaters of the mid-eighteenth century were established in conjunction with the establishment of Italian traveling troupes. Several troupes were formed by musicians active at the Teatro Sant'Angelo, Venice. Although Vivaldi was not personally involved in any of the troupes, the musical imprint of his operas was strong in the mix of pastiches that served several Central European venues. The musical evidence of these performances is almost entirely lost, but the troupes are traceable through libretti. The degree to which the Teatro Sant'Angelo contributed both troupe leaders and troupe musicians stands out among all theaters in Northern Italy. The reach of its musicians, particularly those of the Madonis family, extended to Belgium, France, Hesse, Bavaria, Saxony, Bohemia, Moravia, Poland, and Russia.